2018
DOI: 10.1590/s0100-204x2018000300014
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane bagasse as only roughage for crossbred lactating cows in semiarid regions

Abstract: The objective of this work was to evaluate the effects of different levels of sugarcane bagasse, as exclusive roughage, on nutrient intake and digestibility, feeding behavior, microbial protein synthesis, and dairy performance of crossbred cows. Ten lactating Girolando breed cows (600±34.3 kg body weight) were assigned to a replicated 5×5 Latin square design. The control diet, based on spineless cactus, sugarcane bagasse, and concentrate, was formulated to meet the average production of 20 kg of milk per day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
(16 reference statements)
2
4
3
Order By: Relevance
“…The chemical compostion of WS was typical of wheat grown in Iran (Kahyani et al, 2019a,b), but its nutritive value was poor compared with other research (Eastridge et al, 2009). The chemical composition of SB was similar to that reported by others (Ramli et al, 2005;de Almeida et al, 2018;Freitas et al, 2018). The greater NDF, ADF, and ADL concentrations of SB compared with WS resulted in more fibrous diets when WS was replaced by SB.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The chemical compostion of WS was typical of wheat grown in Iran (Kahyani et al, 2019a,b), but its nutritive value was poor compared with other research (Eastridge et al, 2009). The chemical composition of SB was similar to that reported by others (Ramli et al, 2005;de Almeida et al, 2018;Freitas et al, 2018). The greater NDF, ADF, and ADL concentrations of SB compared with WS resulted in more fibrous diets when WS was replaced by SB.…”
Section: Discussionsupporting
confidence: 65%
“…A high level of uNDF 288 reduces the amount of OM available for degradation in the rumen, and therefore is associated with lesser total-tract digestibility of DM and NDF (Freitas et al, 2018). Other studies have similarly observed a decrease in total-tract digestibility with incorporation of SB in diets (Corrêa et al, 2003;de Almeida et al, 2018;Freitas et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The milk samples were collected on days 19 th and 20 th during both milking periods, after the last collection, and the composed samples were made for each cow. The procedures for analysis of MY and content, as β-hydroxybutyrate (BHBA) concentration in plasma were made as described by Freitas et al (2018).…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the lack of livestock feed resources, it is necessary to identify those factors causing the maximum nutritional efficiency of roughage materials in animal nutrition that can be increasingly used. 1 Approximately 70% of the cost of fattening livestock consists of animal feed and feeding, and the provision of cheap and balanced diets can improve the productivity of this trait. 2 Reducing production costs in the livestock sector is one of the industry's top priorities.…”
Section: Introductionmentioning
confidence: 99%